2003
DOI: 10.1093/ejo/25.1.71
|View full text |Cite
|
Sign up to set email alerts
|

The level of cathepsin B in gingival crevicular fluid during human orthodontic tooth movement

Abstract: This investigation examined gingival crevicular fluid (GCF) levels of lysosomal cystein protease, cathepsin B (CAB), during human orthodontic tooth movement. The study included 10 patients (five males, mean age 22.5 +/- 2.8 years and five females, mean age 23.4 +/- 3.9 years), each having one tooth undergoing orthodontic movement, while the contralateral and antagonist teeth were used as the controls. The GCF was sampled at the control and treatment (compression) sites before activation and at 1, 24, and 168 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 36 publications
1
46
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] The analysis of GCF is a useful and promising method to monitor the changes at a single site during a certain method. 4,5,10 We used the same time intervals of 0, 1, 24, and 168 hours after initiation of orthodontic tooth movement as did previous studies of GCF samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9] The analysis of GCF is a useful and promising method to monitor the changes at a single site during a certain method. 4,5,10 We used the same time intervals of 0, 1, 24, and 168 hours after initiation of orthodontic tooth movement as did previous studies of GCF samples.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,10 We used the same time intervals of 0, 1, 24, and 168 hours after initiation of orthodontic tooth movement as did previous studies of GCF samples. 1,3,6,7 It has been reported that maintenance of oral hygiene is possible during orthodontic treatment. 20 However, other studies have not shown similar results in terms of gingival conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of CAB in as early as 24 hours is reflective of the clinical inflammatory process during the primary stages of orthodontic treatment. 53 The subsequent increment of CAB by 1 month post-treatment is indicative of the biological activity of decomposing the exposed collagen fiber and collagen degradation by-product.…”
Section: 52mentioning
confidence: 99%
“…Moreover, the effect of orthodontic forces on the periodontal ligament is fast, with changes occurring in minutes after their application. 16 It should be considered that the utilization of orthodontic braces may contribute to the increase in dental plaque and gingival inflammation, which might be related to the increased enzymatic activity of in all sites. 13 The hygiene of teeth with orthodontic appliances is difficult and toothbrushing may be complemented by chemical dental plaque control in special situations, such as in patients submitted to orthognathic surgery.…”
Section: Discussionmentioning
confidence: 99%